2011
DOI: 10.1164/rccm.201006-1004oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Quality-Improvement Intervention on End-of-Life Care in the Intensive Care Unit

Abstract: We found this intervention was associated with no improvement in quality of dying and no change in ICU length of stay before death or time from ICU admission to withdrawal of life-sustaining measures. Improving ICU end-of-life care will require interventions with more direct contact with patients and families. Clinical trial registered with www.clinicaltrials.gov (NCT00685893).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
254
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(275 citation statements)
references
References 48 publications
8
254
0
6
Order By: Relevance
“…36 This speaks to the difficulty of changing practice patterns of large groups of providers on an institutional level. 1,[60][61][62] While the intervention team trained hundreds of people at each medical center, many staff had very little contact with the trainers (≤ an hour), which may have diluted the intervention effects. In addition, staff training lasted only 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…36 This speaks to the difficulty of changing practice patterns of large groups of providers on an institutional level. 1,[60][61][62] While the intervention team trained hundreds of people at each medical center, many staff had very little contact with the trainers (≤ an hour), which may have diluted the intervention effects. In addition, staff training lasted only 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, despite being rigorously developed and studied among more than 4000 deaths, few studies have found effects of interventions on family members' ratings of the Quality of Dying and Death (QODD) questionnaire [11], including a large randomized trial of a palliative care intervention [12]. If these and other scales are known to be reliable and to validly measure appropriate constructs, what might explain the discouraging results of studies designed to improve family-reported outcomes?…”
mentioning
confidence: 99%
“…While one large trial of an integrative ICU-based palliative care approach studied in 22 French ICUs was associated with significant decreases in family member anxiety, depression, and post-traumatic stress disorder levels [14], only a handful of ICU-based palliative care studies [15][16][17] have measured family-reported outcomes other than ''family satisfaction''. Moreover, ICU-based palliative care trials have thus far not measured truly patient-centered outcomes, such as symptom scores or quality of life [18].…”
mentioning
confidence: 99%